A scoping review of nursing interventions for reducing the negative impacts of domestic violence among women - Iyus, Yosep; Ai, Mardhiyah; Helmy, Hazmi; Nita, Fitria; Mamat, Lukman; Ahmad, Yamin; Tuti, Pahria (BioMed Central Ltd., 2024)
Background Incidences of domestic violence against women are increasingly every years. Domestic violence has the negative impacts on physical problems, psychological problems, and can even cause death. Nurses have a role for providing interventions to reduce the impact of domestic violence on women. Aim The purpose of this study is to explore methods of nursing interventions in reducing the traumatic effect of domestic violence among women. Method This study used a scoping review method. The literature used in this study from CINAHL, PubMed, and Scopus databases. Search articles used the keywords domestic violence, impact, women, and victims. PRISMA Extension for Scoping Reviews are used for selecting articles. The inclusion criteria for the articles in this study were that the sample was female victims of sexual violence, randomized control trial or quasi-experimental research design, and last 10 years for publications period (2013–2022). Result From three databases, we found 579 articles. After elimination-based inclusion and exclusion criteria, we found 10 articles discussing the effect of nursing interventions in reducing the impact of domestic violence on female victims. Most of the studies from USA and the range of respondents in the articles is 112–1250 respondents. The methods used in providing nursing interventions are classified into three, namely self-management programs, counseling programs, social support programs. The activities carried out in nursing interventions in the form of psychoeducation, relaxation, meditation, and also discussions about solving problems encountered. All articles show that nursing interventions are effective in reducing the impact of domestic violence on women. Conclusion Nurses have an important role to provide comprehensive nursing care to victims of domestic violence by paying attention to various aspects, namely physical, psychological, and spiritual aspects to improve safety and comfort of patients. Implication for Nursing This study is the basis for nurses to provide comprehensive nursing care to reduce the impact of domestic violence among women victims of domestic violence